Analisis dan Perancangan Sistem Informasi Penjadwalan Laboratorium Menggunakan Algoritma Genetika (Jurusan Matematika FMIPA UNNES, 2016)
Scheduling of lectures, especially in the computer lab in a Higher Education is a complex and often experience difficulties, which led to the allocation of subjects, lecturers, and the room is often clashed with the schedule of courses, faculty, and other rooms in the period of the course schedule. There fore, it needs a system and method of optimization that can be applied to develop a schedule of courses. Scheduling optimization can be done by various methods one genetic algorithm. On Genetic Algorithms, the initial population randomly constructed by performing encoding technique, whereas the next population is the result of the evolution of chromosomes through iteration termed generation. Every generation, the chromosomes are going through the evaluation process that will result in the value of fitness. The next stage of selection, crossover and mutation. If the mutation process is carried out and no clashes then finished condition and the best solution is obtained and produces a new chromosome population.